Wear Behavior of Bioactive Glass Coatings Deposited by Thermal Spraying - Monsalve-Arias, Mónica-Johanna; Higuera-Cobos, Oscar-Fabián; Ageorges, Helèn; Vargas-Galvis, Fabio; López-Gómez, María-Esperanza (Universidad Pedagógica y Tecnológica de Colombia, 2022)
In this work, bioactive glass coatings were fabricated by plasma thermal spraying and oxyacetylene flame techniques from 2 different bioactive glass powders with 0 and 2% molar MgO. The metal substrates used were Ti6Al4V alloy and AISI 316L steel. The tribological behavior of the coatings was evaluated by the ball-on-disc method in the presence of simulated biological fluid (SBF), and the results were correlated with their mechanical behavior, obtaining values of hardness (between 4.84 and 5.18 GPa) and fracture toughness (between 5.25 and 6.62 MPa.m1/2). The results show that fracture toughness has a slightly higher effect than hardness on the wear behavior of the coatings under study.